Principles of economics - Mankiw, N. Gregory; Rashwan, Mohamed .H. (Andover, Hampshire : Cengage Learning (EMEA) Limited, 2018)
"The Arab World edition of N. Gregory Mankiw's Principles of Economics is essential reading for economics students in Arab League countries, or those with any interest in Islamic Finance. Following on from the successful second edition, the text contains updated case studies, news articles and features, which focus on the Arab World. It also includes Mankiw's classic ten principles approach to economics - introduced in Chapter one and then referenced throughout the book, designed to help build a framework for understanding. This text is designed to give students the confidence and ability to think like an economist. The third edition is also available as a MindTap, a fully interactive learning platform with additional assessment questions, Concept Clips and case studies."--Provided by publisher.
"In the News and Case Studies have been updated or rewritten to reflect modern approaches to economics in the Arab World. Fully reviewed by local subject matter experts to ensure this edition is appropriate for students. This edition is available as a MindTap with additional assessment questions, global case studies and Concept Clips videos. Examples, case studies, and questions that relate to life in the Arab World show students how concepts relate to their own lives. A chapter on Islamic finance, and how Islamic and non-Islamic banking differ, will be useful for students in the Arab World. Dedicated online resources to allow self-study, concept check and revision, including MindTap with its additional assessment questions, videos and cases."--Provided by Publisher.
Title proper taken from publisher's website.
Includes bibliographical references and index.
Keywords: Economics; Economics -- Islamic countries; Finance -- Islamic countries